Analisis Komparatif Ketimpangan Akses Pelayanan Kesehatan Peserta JKN di Sumatera Utara Berdasarkan Data BPS Periode 2021–2025 - Alya Najwa; Fazri Khoirunnisa Purba; Fitri Annisa; Nabilla Suci Ramadhani; Fitriani Pramita Gurning (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2026)
In an era marked by the expanding coverage of the National Health Insurance (JKN), the utilization of health services remains influenced by disparities in access and the availability of health facilities across various regions. This study aims to analyze whether the expansion of JKN coverage has been accompanied by equitable access to health services in North Sumatra Province during the 2021–2025 period, based on the socioeconomic conditions of the population and the availability of health facilities. This study employs a quantitative approach with a comparative study design based on secondary data sourced from the Central Statistics Agency (BPS) publications for the years 2021–2025. The results indicate that JKN enrollment has increased in areas with high poverty rates, yet the availability of healthcare facilities in those regions tends to remain stagnant or decline. Conversely, regions with higher per capita expenditure exhibit relatively stable or increasing availability of health facilities. This disparity is reflected in the rising unmet health care needs in North Sumatra Province, which increased from 3.83% in 2021 to 5.07% in 2025. Based on the research findings, it can be concluded that the increase in JKN coverage in North Sumatra Province has not been fully accompanied by equitable access to health services. This situation is particularly prevalent in areas with high poverty rates, such as the Nias Islands and Gunungsitoli, which still face limitations in the availability of health facilities and access to adequate healthcare services.